The symbolic-discursive construction of Volodymir Zelensky: updating the hero myth - Pfleger, Sabine (2022)
In this contribution, the figure of Volodymir Zelensky, president of Ukraine, is analyzed as an update of the classical hero archetype. The present work is rooted in Discourse Studies with Cognitive Linguistics tools (van Dijk, 1985; 1990; 2012; Jaworski and Copland 2006; Hart, 2010; Pfleger, 2018; 2021). Through a corpus of ten short speeches in video format, produced and broadcast by Volodymir Zelensky himself, we show the focalized discursive-linguistic features that he uses to portray himself within the framework of an idealized cognitive model (ICM) of hero. We analyze as well the more dynamic discursive-linguistic features that update this model. In the course of the analysis we could show that Volodymir Zelensky shares focalized features with classic mythical heroes, and how he constructs himself as a modern, popular-media hero of the 21st century.